Illustrated Science for Boys and Girls - Anonymous (Salt Lake City, UT : Project Gutenberg, 2008)
"Illustrated Science for Boys and Girls" by Anonymous is a scientific publication written in the late 19th century. The book aims to explore various scientific topics in an accessible and engaging manner targeted primarily at children and young readers. Through a combination of illustrations and informative narratives, it delves into subjects such as journalism, manufacturing processes, and natural phenomena. The opening of the book introduces the topic of newspaper production, highlighting the intricate processes involved in creating a major daily publication. It outlines the various roles integral to the newspaper operation, from editors and reporters to printers and proofreaders, while emphasizing the business side, including costs and revenue from advertisements. The text paints a vivid picture of the bustling environment of a newspaper office, capturing the urgency and excitement of news dissemination, making it clear that a lot of organized effort goes into what readers often take for granted. (This is an automatically generated summary.)
Release date is 2008-06-17
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Technology -- Juvenile literature; Industrial arts